Assessing Interactive Videodisc In Extension - S. Kay Rockwell; James W. King; Thomas G. Tate (Journal of Applied Communications, 1990)
If Extension is going to use interactive videodisc as a program delivery method in the future, the technology must be explored and systematically evaluated in a variety of learning situations.